Economic policy uncertainty and stock market liquidity: Does financial crisis make any difference?. Issue 1 (3rd April 2018) - Debata, Byomakesh; Mahakud, Jitendra
Abstract : Purpose: This study aims to examine the relationship between economic policy uncertainty and stock market liquidity in an order-driven emerging stock market. Design/methodology/approach: Empirical estimates are based on vector autoregressive Granger-causality tests, impulse response functions and variance decomposition analysis. Findings: The empirical findings suggest that economic policy uncertainty moderately influences stock market liquidity during normal market conditions. However, the role of economic policy uncertainty for determining stock market liquidity is significant in times of financial crises. The authors have also observed a significant portion of variation in stock market liquidity that is attributed to investor sentiments during financial crises. Originality/value: This study is original in nature and provides evidence to consider economic policy uncertainty as a possible source of commonality in liquidity in the context of an emerging market.